Ginkgo Biloba Extract Is Comparable With Donepezil in Improving Functional Recovery in Alzheimer’s Disease: Results From a Multilevel Characterized Study Based on Clinical Features and Resting-State Functional Magnetic Resonance Imaging - Zheng, Yu; Xie, Yi; Qi, Ming; Zhang, Ling; Wang, Wei; Zhang, Wanrong; Sha, Liju; Wu, Jiawen; Li, Wanting; Wu, Ting (Frontiers in Pharmacology, 2021)
Background: This study was to explore the efficacy of GBE versus donepezil and their adds-on efficacy on functional recovery. AD patients including 50 in the GBE group, 50 in the Donepezil group and 50 in the combined group were enrolled. Methods: Neuropsychological assessments, including MMSE, ADAS-Cog, IADL, GDS, NPI and QOL-AD were conducted at all follow-ups. Resting-state functional magnetic resonance imaging (rs-fMRI) were collected at baseline and 6-month to compare amplitude of low-frequency fluctuation (ALFF), percent amplitude of fluctuation (PerAF), regional homogeneity (ReHo) and degree centrality (DC) before and after pharmacologic treatment. Results: MMSE and ADAS-Cog scores differed significantly in all groups. The combined group showed significant improvement of GDS scores between baseline and 6-month (p=0.007). The GBE group (p=0.044) and Donepezil group (p=0.012) demonstrated significant improvement between baseline and 6-month in NPI scores. Significant correlations were observed between IADL and ALFF in right gyrus rectus (p=0.03) and in left superior cerebellum gyrus (p=0.01), GDS and ALFF in right middle temporal gyrus (p=0.01), NPI and PerAF in left fusiform gyrus (p=0.03), and MMSE and ReHo in right superior frontal gyrus (p=0.04). Conclusions: To conclude, GBE was comparable with donepezil in the improvement of functional recovery in AD patients while the combined application of GBE and donepezil seems unnecessary. GBE-mediated improvement of functional recovery was characterized by decreased ALFF values in right gyrus rectus and decreased PerAF values in left fusiform gyrus. These featured variation of imaging metrics in specific brain regions may serve as biomarkers in the monitoring of the therapeutic efficacy of GBE. (NCT03090516, http://www.clinicaltrials.gov/)